"If You Report Your Dad, How are You Going to Survive": Health Practitioner Perspectives on Quality of Care for Survivors of Sexual Violence and the Challenge of Family Interference. Issue 7 (April 2022) - Munala, Leso; Welle, Emily; Hohenshell, Emily
This study examined the experiences and perspectives of health practitioners facing the challenges of providing services to female survivors of sexual violence. Interviews were conducted with 28 health practitioners, from eight post-rape care facilities located in Nairobi, Kenya. Data were analyzed using the Colaizzi's 1978 analytical model. The analysis of the results was guided by four domains of the ecological framework: individual, interpersonal, community/cultural, and public policy. The study documented a myriad of detail about the challenges faced by women before reporting the crime as well as the actual process of reporting. One key finding from this study was that health practitioners perceived family interference as a barrier to reporting, access to care, and to the pursuit of justice for survivors, particularly if the perpetrator was a relative. Family interference was also identified as a factor with implications for health practitioners' ability to ensure quality of care as it resulted in patients loss to follow-up and added to the negative emotional toll on health practitioners providing post-rape care. Three main themes emerged in practitioner responses related to this issue: (a) fear of consequences of reporting and care seeking, including economic vulnerability, family conflict, and retaliation such as divorce or further violence, (b) the trend toward out-of-court settlements rather than intervention through formal health and criminal justice sector challenges, and (c) attitudes toward sexual violence and survivors, normalization of rape, and victim-blaming attitudes. The study adds to our understanding of the obstacles faced by health practitioners providing post-rape care and provides a unique set of insights from the front lines on underlying factors contributing to these challenges.